2005
DOI: 10.1021/ac0509049
|View full text |Cite
|
Sign up to set email alerts
|

Giant Magnetoresistive Sensors and Superparamagnetic Nanoparticles:  A Chip-Scale Detection Strategy for Immunosorbent Assays

Abstract: Thin structures of alternating magnetic and nonmagnetic layers with a total thickness of a few hundred nanometers exhibit a phenomenon known as giant magnetoresistance. The resistance of microfabricated giant magnetoresistors (GMRs) is dependent on the strength of an external magnetic field. This paper examines magnetic labeling methodologies and surface derivatization approaches based on protein-protein binding that are aimed at forming a general set of protocols to move GMR concepts into the bioanalytical ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 30 publications
(42 reference statements)
0
78
0
Order By: Relevance
“…Although some efforts have been made to move these concepts into the bioanalytical arena (7)(8)(9)(10)(11)(13)(14)(15), there are few demonstrations of actual magnetic protein assays of either single or multiple analytes in a buffer or serum sample. In particular, multiple analytes require sophisticated biochemistry as well as control sensors on a single chip to ascertain sensitivity and selectivity at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some efforts have been made to move these concepts into the bioanalytical arena (7)(8)(9)(10)(11)(13)(14)(15), there are few demonstrations of actual magnetic protein assays of either single or multiple analytes in a buffer or serum sample. In particular, multiple analytes require sophisticated biochemistry as well as control sensors on a single chip to ascertain sensitivity and selectivity at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…By labeling the target analyte of interest with MNTs (see Fig. 1), analyte detection and quantification can occur when the analyte binds to capture probes on the surface of giant magnetoresistive (GMR) sensors (11)(12)(13)(14)(15) such as spin valve (SV) sensors (16), which have been developed and optimized for use in hard disk drives on a scale of hundreds of millions of units annually with great economy and reliability. Such sensors, when modified for use in biological applications, were previously shown to be capable of detecting as few as 10 MNTs (13,16).…”
mentioning
confidence: 99%
“…They concluded that all sizes of a single magnetic marker can be detected by the GMR sensor provided the sensor size is almost identical to the size of the marker as well as a thin isolated protective layer. Millen et al [39] has proposed the incorporation of GMR structures on bacterial sensing as shown in Figure 12. Surface sensing regions of GMR need to be modified to allow for binding of antibody capture.…”
Section: Gmr Biosensor and Biomedical Applicationmentioning
confidence: 99%
“…The incorporation of GMR structures in bacteria sensing is illustrated in Fig. 13 by Millen, (Millen et al, 2005). Generally, the surface of the GMR sensing region is modified to allow the binding of capture antibody.…”
Section: The Gmr Biosensor and Its Application In Clinical Diagnosticmentioning
confidence: 99%